Pengaruh Kepuasan Petani Ulat Sutera terhadap Loyalitas sebagai Plasma pada Pola Kemitraan Agrowisata Sutera Sari Segara - ADHITA, LUH TRIASTITI MANIK; SUAMBA, I KETUT; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2020)
The Effect of Silkworm Farmer Satisfaction on Loyalty as Plasma on the Silk Agro Tourism Pattern of Sutera Sari Segara Agro Tourism Sutera Sari Segara is an agrotourism that presents natural silk activities, ranging from mulberry tree cultivation to weaving silk thread into silk. Mistakes that generally occur in partnership companies are the creation of partnership agreements by one party, late delivery of production facilities, and late payments. The purpose of this study was to determine the partnership pattern between Sutera Sari Segara Silk Agrotourism and partner farmers and analyze the effect of silkworm farmer satisfaction on loyalty as plasma. Respondents in this study were 40 partner farmers who were obtained based on non-probability sampling with judgmental sampling. The model is designed based on the Structural Equation Modeling (SEM) approach based on SmartPLS version 3.0. The results showed that the partnership pattern between Sutera Sari Segara Silk Agro Tourism and partner farmers was a plasma core pattern. The three service variables have a positive and significant effect on farmer satisfaction. The service variables of cultivation techniques have the greatest influence on farmer satisfaction. The variable farmer satisfaction with loyalty has a positive and significant value. Based on the results of this study, it is expected that Sutera Sari Segara Silk Agro Tourism in making partnership agreements can involve partner farmers. The quality of service provided by the Sari Segara Agrotourism is good. However, it needs to be improved to maintain and improve farmer satisfaction, so that farmers become loyal.